Ethical Therapy Versus Empirical Therapy in Dentistry: Striking the Right Balance (Bangladesh Journal of Medical Science, 2026)
Contemporary dental practice increasingly requires clinicians to balance clinical experience with evidencebased decision-making. Ethical therapy emphasizes patient welfare, scientific evidence, informed consent, and professional integrity, whereas empirical therapy relies primarily on clinical observation and experience. Although empirical approaches have historically contributed to many advances in dentistry, their application without adequate scientific validation may compromise treatment outcomes and patient trust. This editorial discusses the principles, advantages, and limitations of both approaches and highlights the importance of integrating clinical expertise with current evidence. The future of dentistry lies in ethical, evidence-based, and patient-centered care that combines scientific rigor with sound clinical judgment.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S189-S191